2015
DOI: 10.17219/acem/28626
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins and Their Use in Children

Abstract: Immunoglobulin preparations are one of the products of the human plasma fractionation, where the plasma is obtained, in accordance with WHO guidelines from at least 1,000 donors. These preparations contain all IgG subclasses with various antigen characteristics. In clinical practice these drugs are used as replacement therapy in patients with primary and secondary immunodeficiencies as well as immunomodulatory therapy in many autoimmune diseases and systemic inflammatory diseases. Here we present characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…For more than 20 years, immunoglobulins are widely used as a modulatory factor in the treatment of autoimmune and inflammatory diseases that represent a common finding in primary immunodeficiecies. 23 , 24 Patient 01 was affected by Evans syndrome in the context of 22q11 deletion. IVIg, even through at replacement dose (400 mg/kg/28 days) improved his clinical disease course.…”
Section: Discussionmentioning
confidence: 99%
“…For more than 20 years, immunoglobulins are widely used as a modulatory factor in the treatment of autoimmune and inflammatory diseases that represent a common finding in primary immunodeficiecies. 23 , 24 Patient 01 was affected by Evans syndrome in the context of 22q11 deletion. IVIg, even through at replacement dose (400 mg/kg/28 days) improved his clinical disease course.…”
Section: Discussionmentioning
confidence: 99%
“…The mean frequency of AE seen during IVIG treatment was reported to be 20% changing from 1 to 81%. [7][8][9][10] Galli et al 19 reported 40% of AE seen in PID children. In addition, Dashti-Khavidaki et al 20 documented 216 AE (7.2%) in 3,004 infusions for 13 years.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] The frequency of adverse events seen in IVIG treatment varies between 1-81% with a mean value of 20%. [7][8][9][10] These are classified as early or late according to the time of occurrence of the reaction. 11 The most common early adverse events (AE) are fever, chills, headache, nausea, hypotension, myalgia, wheezing, back pain and rash.…”
mentioning
confidence: 99%
See 1 more Smart Citation